Software Quality Models: A Comprehensive Review and Analysis - M. Sadeghzadeh Hemayati; H. Rashidi (Journal of Electrical and Computer Engineering Innovations, 2017)
Background and Objectives: One of the major challenges in software engineering is how to respond to the desolate state of high-quality software development in a timely and cost-effective manner. Many studies have been conducted in an attempt to formalize the quality of software. However, according to the recent researches, the lack of comprehensive quality model is rooted in neglecting all quality aspects. Methods: In this study, we review nineteen quality models and classify them from three different perspectives, including structural, behavioral, and basic and derived aspects. The main aim is to specify and extract the more comprehensive set of quality factors to evaluate software quality. Results: This paper compares the different quality models and analyzes the factors to draw the necessary aspects in comprehensive quality models. Since the software quality involves several engineering tasks and several players who deal with quality concepts during software life cycle according to their various roles, in various phases and different artifacts, comprehensive quality models must consider many factors. Conclusion: These factors are in different aspects such as the measurement time in different development phases, product as well as process-related quality factors, a set of quality metrics measureable on the different type of artifacts such as document, model and source code, and finally a specific mechanism to apply dynamic weights to quality factors to determine their impacts on final quality of a product based on its application domain. ======================================================================================================Copyrights©2018 The author(s). This is an open access article distributed under the terms of the Creative Commons Attribution (CC BY 4.0), which permits unrestricted use, distribution, and reproduction in any medium, as long as the original authors and source are cited. No permission is required from the authors or the publishers.======================================================================================================